2017
DOI: 10.11124/jbisrir-2017-003345
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of community-dwelling older adults with the use of telecare in home care services: a qualitative systematic review

Abstract: The experiences with the use of telecare are diverse. Findings indicate telecare systems can promote safety and security to age in place that is a wish of many older adults. However, "one size does not fit all"- Telecare systems must fit individual needs, and be supported by service providers to accommodate sustainable use over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…Older adults experienced increased safety, security and improved independence when using telecare over time. This is supported by previous studies (Karlsen et al, ) but usually applied to first‐generation telecare systems and the participants were not followed up over time, in most of these studies. The present study shows findings from a range of telecare devices and from older adults with different needs in various contexts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Older adults experienced increased safety, security and improved independence when using telecare over time. This is supported by previous studies (Karlsen et al, ) but usually applied to first‐generation telecare systems and the participants were not followed up over time, in most of these studies. The present study shows findings from a range of telecare devices and from older adults with different needs in various contexts.…”
Section: Discussionsupporting
confidence: 66%
“…Telecare may contribute to increased safety and independence to community‐dwelling older adults, as it can facilitate assistance in case of accidents (Karlsen, Ludvigsen, Moe, Haraldstad, & Thygesen, ). Moreover, a recent study by Rostill et al (), shows promising results of testing an Internet of Things system for dementia care, a system that intends to identify changes in a person's health or routine, to prevent the development of more serious complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flere studier basert på perspektiver fra helsepersonell (Johannessen, Storm & Holm, 2019;Radhakrishnan, Jacelon & Roche, 2012) og brukerne selv (Berge, 2017;Eriksson, Lindstrøm, & Ekenberg, 2011;Karlsen, Ludvigsen & Moe et al, 2017) viser at bruk av velferdsteknologi gir økt opplevelse av trygghet og sikkerhet. En nylig publisert studie viser imidlertid til at begrensninger ved teknologien og vanskeligheter med å benytte og forstå de teknologiske løsningene oppleves som utfordrende for de eldre brukernes sikkerhet (Johannessen et al, 2019).…”
Section: Innledningunclassified
“…The lived experience of aging in place is not well documented in existing systematic reviews. Although there are several published systematic reviews examining the provision of specific services for community-dwelling older adults, such as home health care or telecare [ 8 , 9 ], only two systematic reviews focus specifically on aspects of aging in place: a systematic review of quantitative studies on cost effectiveness of aging in place [ 10 ], and a systematic review of factors influencing acceptance of technology for aging in place [ 11 ]. The authors of the cost effectiveness review [ 10 ] found the existing evidence to be low quality and limited by inconsistencies in measurement, so they were unable to draw any robust conclusions.…”
Section: Introductionmentioning
confidence: 99%